The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/c9ra08678a
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Ag3PO4/GO on 3D nickel foam and its photocatalytic degradation of norfloxacin antibiotic under visible light

Abstract: A series of Ag3PO4/graphene oxide catalysts were dip-coated onto 3D nickel foam for photocatalytic degradation of norfloxacin antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The energy dispersive X-ray spectroscopy (EDS) analysis demonstrates the uniform distribution of Ti and O over the surface of Ni branch (Figure S1). Two distinctive photoluminescence characteristic peaks at the vicinity of ∼330.0 and ∼725.0 eV are independently allocated to TiO 2 and Ni, respectively (Figure S1). In addition, the characteristic Raman peaks at 143.0, 196.0, 399.0, 525.0, and 638.0 cm –1 (Figure S1) are respectively assigned to E 1g , E 2g , B 1g , A 1g /B 1g , and E g vibrational TiO 2 modes .…”
Section: Resultsmentioning
confidence: 88%
“…The energy dispersive X-ray spectroscopy (EDS) analysis demonstrates the uniform distribution of Ti and O over the surface of Ni branch (Figure S1). Two distinctive photoluminescence characteristic peaks at the vicinity of ∼330.0 and ∼725.0 eV are independently allocated to TiO 2 and Ni, respectively (Figure S1). In addition, the characteristic Raman peaks at 143.0, 196.0, 399.0, 525.0, and 638.0 cm –1 (Figure S1) are respectively assigned to E 1g , E 2g , B 1g , A 1g /B 1g , and E g vibrational TiO 2 modes .…”
Section: Resultsmentioning
confidence: 88%
“…Wang et al [ 80 ] synthesized the magnetic NiFe 2 O 4 /CS composite by the hot water method to activate persulfate for the elimination of levofloxacin. When the levofloxacin degradation was carried out under the optimized condition, with 0.6 g/L NiFe 2 O 4 /CS composite and 1.8 g/L persulfate being added and the initial pH being adjusting to 5, 67%, levofloxacin was degraded within 1 h. Yang’s research group found that the recycling challenge was solved by preparing different graphene oxide loaded Ag 3 PO 4 /GO film catalysts, and the degradation rate of norfloxacin was about 83.68% in 100 min and the reaction rate constant k was 1.9 times that of pristine Ag 3 PO 4 [ 81 ].…”
Section: Removal Of Pharmaceuticalmentioning
confidence: 99%
“…Norfloxacin is another class of fluoroquinolone synthetic antibiotics used in veterinary medicine and human infection treatment. It can cause serious health issues because of its teratogenic, mutagenic, and embryotoxic nature . Various binary and ternary composites are reported for this drug decomposition.…”
Section: Detoxification Of Edsmentioning
confidence: 99%
“…Various binary and ternary composites are reported for this drug decomposition. Photogenerated electrons of Ag 3 PO 4 were efficiently separated through conductive graphene oxide (GO) in the Ag 3 PO 4 /GO film catalyst supported on Ni foam, and the generated active O 2 •– and • OH radicals were involved in norfloxacin degradation . Conductive GO extracts the electrons from the CB of Ag 3 PO 4 to prevent recombination.…”
Section: Detoxification Of Edsmentioning
confidence: 99%
See 1 more Smart Citation